Current Pharmaceutical Treatments and Alternative Therapies of Parkinson’s Disease - Dong, Jie; Cui, Yanhua; Li, Song; Le, Weidong (Current Neuropharmacology, 2016)
Over the decades, pharmaceutical treatments, particularly dopaminergic (DAergic) drugs have been considered as the main therapy against motor symptoms of Parkinson's disease (PD). It is proposed that DAergic drugs in combination with other medications, such as monoamine oxidase type B inhibitors, catechol-O-methyl transferase inhibitors, anticholinergics and other newly developed non-DAergic drugs can make a better control of motor symptoms or alleviate levodopa-induced motor complications. Moreover, non-motor symptoms of PD, such as cognitive, neuropsychiatric, sleep, autonomic and sensory disturbances caused by intrinsic PD pathology or drug-induced side effects, are gaining increasing attention and urgently need to be taken care of due to their impact on quality of life. Currently, neuroprotective therapies have been investigated extensively in pre-clinical studies, and some of them have been subjected to clinical trials. Furthermore, non-pharmaceutical treatments, including deep brain stimulation (DBS), gene therapy, cell replacement therapy and some complementary managements, such as Tai chi, Yoga, traditional herbs and molecular targeted therapies have also been considered as effective alternative therapies to classical pharmaceutics. This review will provide us updated information regarding the current drugs and non-drugs therapies for PD.
Keywords: non-motor symptoms